Dilema Penerapan Hukuman Kebiri Kimia bagi Pelaku Kekerasan Seksual terhadap Anak di Indonesia - Firdaus Syamsiar Ramadhan; Aturkian Laia (INDO PUBLISHING, 2026)
Child sexual abuse as an extraordinary crime prompted the issuance of chemical castration policies under Law No. 17/2016 and Government Regulation No. 70/2020. However, its implementation triggers legal dilemmas regarding human rights and medical ethics. This normative legal research aims to analyze the regulations, implementation dilemmas, countermeasure effectiveness, and future ideal legal models of chemical castration. The results indicate that chemical castration is designated as a rehabilitative measure (maatregel), not retribution. This sanction conflicts with the prohibition of torture under Article 28G Paragraph (2) of the 1945 Constitution, medical ethics rejection, and limited clinical assessment infrastructure. This study recommends a comprehensive policy reconstruction: restricting application only to offenders with paraphilic disorders, establishing independent specialized medical teams, and strengthening rehabilitation alongside victim recovery systems.